Perancangan Aplikasi E-Commerce (Studi Kasus: Distributor Coklat Bandung) - Siti Mukaromah; Dadi Rosadi (Jurnal Computech & Bisnis (e-Journal), 2015)
The design of e-Commerce Application is a system created to improve and develop the existing systems in the field of chocolate sales. The management system is expected to increase turnover and expand the areas of product marketing at distributor chocolate chocolate sales. To make electronic sales information system based e-commerce using PHP, MySql as programming languages, and XAMPP for a web server, which can be used in the Windows XP operating system where the system has a browser that can display web pages. The method used for the development of the system by using the methodology OOSE (Object Oriented Software Enggeneering). Phases which makes the model requirements and analysis, design and implementation, and testing models. This site displays the catalog menu chocolate accompanied by detailed pictures, prices, and messages. Consumers can choose products that will be ordered and store it in the shopping cart. If the consumer has ordered goods are selected, then the consumer must fill in the form with the complete identity of the buyer to confirm receipt of payment and delivery of goods to the address. Payment can be made by transferring money to a bank account number that has been determined.  Keywords:: e-commerce; sales; chocolate